Integrative approach to describe new species of squat lobsters of the genera Heteronida Baba & de Saint Laurent, 1996 and Torbenella Baba, 2008 (Decapoda, Munididae) from the Southwestern Pacific Ocean - Enrique Macpherson; Paula C. Rodríguez-Flores; Annie Machordom (European Journal of Taxonomy, 2023)
Specimens of munidid squat lobsters belonging to the genera Heteronida Baba & de Saint Laurent, 1996 and Torbenella Baba, 2008 were collected in scientific expeditions made by several French cruises along the southwestern Pacific. These specimens were identified as two species (one new) of Heteronida and six species (four new) of Torbenella. The present paper provides systematic accounts of the five new species, along with new locality records of known species shown by this material and color information where available. Molecular data is provided to support the systematic status of each new species. A key to species for each of the genera is also presented.